P-489 The ABC of fertility intentions: a mixed-methods study exploring the spectrum of attitudes towards family building. (30th June 2022) - Shawe, J; Grace, B; Stephenson, J
Abstract: Study question: What are the intentions of men and women of reproductive age in the UK regarding fertility and family building? Summary answer: We identified six main categories of people; Avoiders, Betweeners, Completers, Desirers, Expectants and Flexers, for whom fertility-education strategies should be tailored differently to suit intentions. What is known already: Several studies have highlighted poor fertility awareness across men and women of reproductive age. As the average age of first-time parents continues to rise, there has been a concerted effort from educators, healthcare professionals, charities, reproductive health groups and government policy makers, to improve fertility awareness. In order to ensure that these messages are effective and to deploy the best strategies, it is important to understand people's reproductive health needs. This study therefore aimed to explore the different family building intentions in order to aid tailoring of information to help individuals and couples achieve their family building intentions. Study design, size, duration: Mixed method research was conducted via a UK-wide cross-sectional survey and semi-structed interviews. Results were obtained from 1, 082 survey respondents and in-depth interviews with 15 men and 20 women. Interviewees were purposively sampled to include men and women from the reproductive age range (18-45 years) and of varying ethnic and educational backgrounds. Participants/materials, setting, methods: Survey participants were recruited nationwide via online newspaper and social media adverts and of those who agreed to a follow-up interview, 35 were included this study. Interviews lasted an hour on average. Data was transcribed and analysed via thematic framework analysis. Favourable ethical opinion was given by University College London Research Ethics Committee. Main results and the role of chance: From the survey and interviews, we identified six key categories of people, grouped alphabetically, in a user-friendly manner to highlight a spectrum of fertility intentions: Avoiders describe respondents who have no children and do not want to have children in the future; Betweeners describe those who already have child(ren) and want more in the future but are not actively trying to conceive; Completers describe those who have child(ren) but do not want more; Desirers describe those who are actively trying to conceive; Expectants describe those who were pregnant at the time of the study and Flexers describe those who may or may not already have and are unsure but open to having child(ren) in the future. A majority of the survey population were trying to get pregnant; were pregnant; or planning to have a child in the future - whether actively, passively or simply open to the idea, with interviews providing deep insights into their family building decision-making. Limitations, reasons for caution: Due to the online recruitment method, there may be a bias toward more educated respondents. Wider implications of the findings: We developed a user-friendly, alphabetical categorisation of fertility intentions, which can be used by individuals, healthcare professionals, educators, special interest groups, charities, and policymakers to support and enable individuals and couples in making informed choices to achieve their desired intentions, if and when they choose to start a family. Trial registration number: not applicable